Impact of a Reference Center on Leprosy Control under a Decentralized Public Health Care Policy in Brazil. - Raquel Rodrigues Barbieri; Anna Maria Sales; Mariana Andrea Hacker; José Augusto da Costa Nery; Nádia Cristina Duppre; Alice de Miranda Machado; Milton Ozório Moraes; Euzenir Nunes Sarno (Public Library of Science (PLoS), 2016)
OBJECTIVE:We evaluated the profile of patients referred to the Fiocruz Outpatient Clinic, a reference center for the diagnosis and treatment of leprosy in Rio de Janeiro, RJ, and analyzed the origins and outcomes of these referrals. METHODS:This is an observational retrospective study based on information collected from the Leprosy Laboratory database at Fiocruz, Rio de Janeiro, RJ, Brazil. A total of 1,845 suspected leprosy cases examined at the reference center between 2010 and 2014 were included. The originating health service referrals and diagnostic outcomes were analyzed as well as the clinical and epidemiological data of patients diagnosed with leprosy. RESULT:Our data show that the profile of the patients treated at the Clinic has changed in recent years. There was an increase in both the proportion of patients with other skin diseases and those who had visited only one health service prior to our Clinic. Among the total 1,845 cases analyzed, the outcomes of 1,380 were linked to other diseases and, in 74% of these cases, a biopsy was not necessary to reach a diagnostic conclusion. A decrease in new leprosy case detection among our patients was also observed. Yet, among the leprosy patients, 40% had some degree of disability at diagnosis. CONCLUSION:The results of the present study demonstrated the importance of referral centers in support of basic health services within the decentralization strategy. But, the success of the program depends on the advent of new developmental tools to augment diagnostic accuracy for leprosy. However, it should be emphasized that for new diagnostic methods to be developed, a greater commitment on the part of the health care system regarding research is urgently needed.